2021
DOI: 10.3390/ijerph181910422
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Cross-Cultural Adaptation and Psychometric Properties of Oral Health Literacy Tools

Abstract: The aims of this systematic review were to critically appraise the quality of the cross-cultural adaptation and the psychometric properties of the translated versions of oral health literacy assessment tools. CINAHL (EBSCO), Medline (EBSCO), EMBASE (Ovid), and ProQuest Dissertation and Thesis were searched systematically. Studies focusing on cross-cultural adaptation and psychometric properties of oral health literacy tools were included. The methodological quality of included studies was assessed according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 73 publications
(198 reference statements)
0
13
0
Order By: Relevance
“…Yet, a disproportionately higher share of OHL studies is conducted in high-income countries and the majority of tools were developed in English, which raises concerns about a potential lack of cultural and linguistic sensitivity in multicultural and non-English-speaking contexts. [1,14] Brazil is a unique case of a densely populated and diverse country with marked social gradients in oral health and a dynamic healthcare system. [15] A relatively recent expansion of public dental services has contributed to facilitating the access of lower-income groups to dental treatments, although important barriers remain to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, a disproportionately higher share of OHL studies is conducted in high-income countries and the majority of tools were developed in English, which raises concerns about a potential lack of cultural and linguistic sensitivity in multicultural and non-English-speaking contexts. [1,14] Brazil is a unique case of a densely populated and diverse country with marked social gradients in oral health and a dynamic healthcare system. [15] A relatively recent expansion of public dental services has contributed to facilitating the access of lower-income groups to dental treatments, although important barriers remain to be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review examining the articles in 16 health literacy tools showed that most of the included studies had methodological flaws, did not follow all the steps of cross-cultural adoption, and thus, most included studies were rated as low-quality. 25…”
Section: Discussionmentioning
confidence: 99%
“…Over a decade, oral health literacy (OHL) has gathered significant interest from healthcare professionals and policymakers due to its considerable effect on oral health outcomes [ 12 , 13 ]. Considered a multifaceted concept, OHL has consistently been examined in dental research [ 13 , 14 ] and is indicated as a potential determinant of oral health behaviors, outcomes, and access to dental services [ 14 ].…”
Section: Introduction and Aimsmentioning
confidence: 99%